TARI PALANG YUDHO SEBAGAI REPRESENTASI TRANSFORMASI BUDAYA KABUPATEN MADIUN - Rahma Raffi Aristawati; Arif Hidajad; Eko Wahyuni Rahayu (Greget: Jurnal Kreativitas dan Studi Tari, 2025)
This article examines the process transformation of local cultural traditions into a modern dance work titled Tari Palang Yudho, a choreography inspired by two major cultural identities of Madiun: the Dongkrek performance tradition and pencak silat. The study aims to analyze how these cultural sources are transformed into new artistic expressions through the processes of reinterpretation, stylization, and symbolic reconstruction. Using a qualitative descriptive approach, data were collected through observation, interviews with the choreographer Pipin Dwi Pangesti and cultural practitioners in Madiun, as well as documentation studies. The findings indicate that the creation of Palang Yudho demonstrates a multidimensional cultural transformation, including the transformation of form, function, and meaning. Dongkrek, traditionally functioning as a ritual to ward off calamity, is reconstructed into a theatrical dance form, while pencak silat is adapted into stylized movement vocabulary to strengthen the identity of Madiun as Indonesia’s Village of Fighters. The transformation also occurs in musical composition, costume, and narrative structure to produce a contemporary aesthetic that remains rooted in local cultural values. This study highlights that Palang Yudho serves not only as a creative work but also as a cultural strategy for preservation, revitalization, and cultural representation in the modern performing arts landscape.